THE INFLUENCE OF TECHNOLOGY USE, LEARNING INDEPENDENCE, AND STUDENT ACTIVITY ON ECONOMIC LEARNING OUTCOMES IN THE COVID-19 PANDEMIC TIME AT SMA NEGERI 9 BOGOR - Fira, Shafira; Wibowo, Agus; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine the effect of the use of technology, independent learning, and the activeness of students on learning outcomes both partially and simultaneously. In particular, this study uses a quantitative research method with a survey method using a questionnaire. The data analysis technique used in this study is multiple regression analysis. The research sample was 179 students, Based on the results of the study, the use of technology, independent learning, and student activity have an influence on learning outcomes. In the t-test the use of technology in learning partially has a positive and significant effect on the economics learning outcomes of class XI IPS students at SMA Negeri 9 Bogor with a tcount of 8.349 . greater than t table which is equal to 1.973 (tcount > ttable ), learning independence in learning partially has a positive and significant effect on the economics learning outcomes of class XI IPS students at SMA Negeri 9 Bogor with a tcount of 7.696. is greater than ttable which is equal to 1.973 (tcount > ttable ), and student activity in learning partially has a positive and significant effect on the economics learning outcomes of class XI IPS students at SMA Negeri 9 Bogor by having tcount 6.647. greater than t table which is equal to 1.973 (tcount > ttable ).